Performance and Environmental Impacts Review of Li-Fi and Wi-Fi Technologies - Christoforus Williem Deo Lumoindong; Andre Muslim; Burawi Mohamed Nasreddin; Mia Galina (Journal of Environmental Engineering and Waste Management, 2018)
Nowadays, internet connectivity is one of the staple things in human lifestyle, especially for those who live in cities. There are a lot of ways to connect to the internet, and one of them is using Wi-Fi (Wireless Fidelity) connection. Wi-Fi connection is seen as the most reliable connection, until Li-Fi (Light Fidelity) technology is coined in 2011. Li-Fi uses visible light as data transfer medium instead of radio frequency (RF) signal used by Wi-Fi. Theoretically, Li-Fi is able to reach hundred times of Wi-Fi connection speed due to their use of light as data transfer medium. Li-Fi is also expected as a solution to environmental problems caused by Wi-Fi. The RF signal used by Wi-Fi can cause some environmental problems such as growth inhibition and diseases to organisms including humans. The visible light used by Li-Fi is expected to cause minimal effects to the environment, as Li-Fi uses common LED light bulbs which are used as home lighting apparatus.  Li-Fi is commonly seen as a ‘greener’ technology compared to Wi-Fi. In this review, the performance and environmental impacts of both Wi-Fi and Li-Fi are analysed to determine whether Li-Fi is really capable to be a ‘greener’ replacement to Wi-Fi technology